The Effect of Green Innovation, Environmental Awareness, and Competitive Advantage on MSME Marketing Performance - Sumarlin, Fawwaz Akbarrama; Nuvriasari, Audita (LifeSciFi, 2024)
Environmental issues and the reduction of natural resources are factors for MSMEs to develop environmentally friendly products. The high level of public awareness of environmental health is one of the factors that drives changes in behavioral consistency in using green products, which of course has an impact on the marketing performance of green product MSMEs. Several factors that influence marketing performance are green innovation, environmental awareness and competitive advantage. Therefore, this study aims to analyze the influence of green innovation, environmental awareness and competitive advantage on the marketing performance of green products of MSMEs in the Special Region of Yogyakarta. The sample in this study was 45 MSMEs. The sampling technique was carried out using the non-probability sampling method, namely purposive sampling. The results of the instrument test in this study were declared valid and reliable. The results of the classical assumption test stated that the research data was normally distributed and produced a regression model that was free from multicollinearity and heteroscedasticity. The results of this study prove that green innovation has a positive and significant effect on marketing performance. Environmental awareness does not have a significant effect on marketing performance. Competitive advantage does not have a significant effect on marketing performance.